Agonistic Entanglements of Art and Activism: #RhodesMustFall and Sethembile Msezane's Chapangu Performances. Issue 3 (2nd September 2019) - Pauwels, Matthias
ABSTRACT: This article reflects on some of the limitations and challenges of recent student protest movements in South Africa, with a specific focus on their activism on issues of cultural politics. It articulates the dominant modes of cultural activism of these movements, taking the #RhodesMustFall campaign as a defining instance in this regard. Revisiting one of the first victories of #RhodesMustFall, the removal of the statue of Cecil John Rhodes from the University of Cape Town's main campus in 2015, it finds that another, very different and, in many ways, opposing form of cultural activism asserted itself in an artistic performance by Sethembile Msezane. It is argued that during this iconic scene of contemporary student protests, an uneasy tension thus came to exist, provoking fundamental questions regarding activist styles of cultural contestation and modes of subjectivity. Through Jacques Rancière's notion of the politics of aesthetics, Msezane's performance is taken to harbour a critique of the dominant activist modes of #RhodesMustFall, affirming the important role of creativity and imagination within radical political movements. Inversely, a critique of artistic interventions from the perspective of a #RhodesMustFall style of cultural activism is formulated, based on Fredric Jameson's redemptive reading of philistine attitudes. Although #RhodesMustFall and Msezane's performance are thus conceived in agonistic terms, it is argued that the tension between art and activism should be endorsed as a productive one, allowing for processes of self-critique, self-correction, and self-reinvention within social protest movements.